Did Going North Give Us Migraine? An Evolutionary Approach on Understanding Latitudinal Differences in Migraine Epidemiology - Viganò, Alessandro (Headache, 2019)
This commentary discusses a recent publication by evolutionary biologists with strong implications for migraine experts. The Authors showed that a gene polymorphism associated with migraine gave our ancestors an evolutionary advantage when colonizing northern, and thus colder, territories. They then highlight that the prevalence of migraine may differ among countries because of climatic adaptation. These results may prove useful in planning both epidemiological and physiological studies in the field of migraine.